Refractive index dispersion properties of Cr-doped ZnO thin films by sol-gel spin coating method - Aydin, H.; Aydin, C.; Al-Ghamdi, Ahmed A.; Farooq, W. A.; Yakuphanoğlu, Fahrettin (Elsevier Gmbh, 2016)
The undoped ZnO and the Cr-doped ZnO nanomaterials were prepared by the sol gel spin coating technique. The effects of chromium on the structural, morphological and optical properties of the zinc oxide films were investigated. The ZnO samples were characterized by atomic force microscopy (AFM), X-ray diffraction (XRD) and UV-vis-NIR spectrophotometer. XRD patterns of Cr doped ZnO samples were identified with a hexagonal wurtzite structure of ZnO. Atomic force microscopy results indicate that the Cr doped ZnO films have the nanostructure. The influence of the Cr doping on the film growth is resulted in a change of grain size. The optical band gap of the films was calculated by optical absorption method. The optical band gap of the ZnO films was significantly changed by Cr dopant. The obtained results indicate that the structural and optical properties of ZnO films can be controlled with Cr doping. (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: ZnO; Nanomaterials; Sol-gel technique